2019
DOI: 10.1101/692004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic immunodeficiency and autoimmune disease reveal distinct roles of Hem1 in the WAVE2 and mTORC2 complexes

Abstract: One sentence summary: Hem1 loss of function mutations cause a congenital immunodysregulatory disease and reveal its role regulating WAVE2 and mTORC2 signaling. AbstractImmunodeficiency often coincides with immune hyperresponsiveness such as autoimmunity, lymphoproliferation, or atopy, but the molecular basis of this paradox is typically unknown. We describe four families with immunodeficiency coupled with atopy, lymphoproliferation, cytokine overproduction, hemophagocytic lymphohistocytosis, and autoimmunity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This has severe consequences for the host, as inefficiently cleared pathogens, apoptotic and necrotic cell bodies are a major source of inflammation and rise of autoantigens, respectively. Indeed, numerous studies have suggested that inefficiently cleared cells can promote the development of autoimmune diseases, such as observed in recently described human patients harboring Hem1 mutations (102).…”
Section: Fc Gamma Receptor (Fc R)-induced Phagocytosis Is Mainly Accomentioning
confidence: 99%
“…This has severe consequences for the host, as inefficiently cleared pathogens, apoptotic and necrotic cell bodies are a major source of inflammation and rise of autoantigens, respectively. Indeed, numerous studies have suggested that inefficiently cleared cells can promote the development of autoimmune diseases, such as observed in recently described human patients harboring Hem1 mutations (102).…”
Section: Fc Gamma Receptor (Fc R)-induced Phagocytosis Is Mainly Accomentioning
confidence: 99%
“…Recently, 5 patients have been identified with loss-of-function mutations in NCKAP1L [74]. These bi-allelic missense mutations lead to either a loss of HEM1 protein or abrogated binding of HEM1 to the GTPase ADP-ribosylation factor 1, thereby leading to destabilization of the WRC or disruption of ADP-ribosylation factor 1-WRC binding and activation, respectively.…”
Section: Pids Caused By Defective Cytoskeletal Regulationmentioning
confidence: 99%
“…This defective F-actin accumulation was also observed in the NK-cell-target synapse. Reduction of the cortical actin barrier in HEM1-deficient T-cells resulted in exaggerated degranulation and IL-10, perforin, and granzyme A and B release, which could explain the patients’ autoinflammatory phenotype [74]. Increased degranulation has also been observed in ARPC1B-deficient [31] and MKL1-deficient [28] neutrophils.…”
Section: Pids Caused By Defective Cytoskeletal Regulationmentioning
confidence: 99%
See 2 more Smart Citations